2021
DOI: 10.1039/d0nr08108f
|View full text |Cite
|
Sign up to set email alerts
|

CoP2/Fe-CoP2 yolk–shell nanoboxes as efficient electrocatalysts for the oxygen evolution reaction

Abstract: Development of an efficient electrocatalyst is an important requirement for water splitting systems to produce clean and sustainable hydrogen fuel. Herein, we synthesized CoP2/Fe-CoP2 yolk-shell nanoboxes (YSBs) as efficient electrocatalysts...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…6e, the catalytic performance of (Ni,Fe) 2 P/C HNRs is compared to many other phosphide- based electrocatalysts. 19,[32][33][34][35][36][37][38][39][40] As shown in Fig. 6f, both the TOF (0.00271 s −1 ) and mass activity (48.9 A g −1 ) of (Ni,Fe) 2 P/C HNRs at an overpotential of 260 mV are substantially greater than those of (Ni,Fe) 2 P/C NPs, Ni 2 P NPs, Fe 2 P and commercial RuO 2 .…”
Section: Resultsmentioning
confidence: 89%
“…6e, the catalytic performance of (Ni,Fe) 2 P/C HNRs is compared to many other phosphide- based electrocatalysts. 19,[32][33][34][35][36][37][38][39][40] As shown in Fig. 6f, both the TOF (0.00271 s −1 ) and mass activity (48.9 A g −1 ) of (Ni,Fe) 2 P/C HNRs at an overpotential of 260 mV are substantially greater than those of (Ni,Fe) 2 P/C NPs, Ni 2 P NPs, Fe 2 P and commercial RuO 2 .…”
Section: Resultsmentioning
confidence: 89%
“…Based on the combination of theoretical and experimental investigations, hybridization of a bimetallic phosphide with the nitrogen-doped carbon matrix significantly enhances the EWS activity by regulating the electronic structure and surface energy of the electrocatalysts. The morphological and structural modification by the construction of porous, hollow, or core-shelled nanostructures is another valid strategy to further enhance the EWS performance of CoP X -based electrocatalysts. , For example, the construction of an electrocatalyst with a core-shelled structure is one of the most effective strategies for performance improvement. The core-shelled electrocatalyst possesses a unique morphology with a hollow shell wrapped around a core, providing more accessible active sites and faster ion/electron transfer for redox reactions. …”
Section: Introductionmentioning
confidence: 99%
“…Hollow nanostructures are another vital approach to enhance the performance of OER applications owing to their unique structural features. , Among various material architectures, multishelled hollow structures exhibit several advantages, such as a large surface area and reduced diffusion lengths for mass transport. , In particular, the high surface areas of hollow multishelled structures can provide large accessible active sites for redox reactions. Wang et al reported the synthesis of Co 3 O 4 /Co-Fe oxide double-shelled nanoboxes that exhibit high performance for OER . Due to their unique features, metal–organic frameworks (MOFs) provide various opportunities for the construction of hollow materials with a controllable structure, well-defined internal voids, a low density, a large surface area, and abundant active sites. In a previous literature study, CoP 2 /Fe-CoP 2 yolk-shell nanoboxes were successfully synthesized from ZIF-67 nanocubes (MOF), and they showed excellent OER performance . Nevertheless, an enhanced OER activity can be achieved by designing a complex hollow structure with tunable chemical compositions.…”
Section: Introductionmentioning
confidence: 99%
“…27−31 In a previous literature study, CoP 2 /Fe-CoP 2 yolkshell nanoboxes were successfully synthesized from ZIF-67 nanocubes (MOF), and they showed excellent OER performance. 32 Nevertheless, an enhanced OER activity can be achieved by designing a complex hollow structure with tunable chemical compositions. Apart from the morphology, the rational design of heterostructures constructed using various transition-metal electrocatalysts, especially with strong coupling interfaces and the synergistic effect between them, could regulate the electron transfer and active sites.…”
Section: Introductionmentioning
confidence: 99%